Art in public spaces - Fusil, Natasha; Shoben, Andrew; Zakariya, Khalilah (2017)
Christmas is around the corner, and with a few of us planning to do a little cuti cuti Malaysia, cities like Penang and Ipoh may be coming out tops for a few reasons.. One of the biggest tourisms draws for the past few years have been the bevy of large scale murals and graffiti paintings scattered around heritage sites in the city. It’s added colour and life into the streets and buildings that were previously forgotten and of course, it’s makes for a fun photo op. But selfies aren’t the main reason these pieces of art in the public. To go beyond the broad strokes, we speak to Professor Andrew Shoban from Goldsmiths university London and Dr. Khalilah Zakariya from International Islamic University Malaysia.